Long-term versus short-term consistency in the grapheme-colour synaesthesia: Grapheme-colour pairings can change in adulthood - Chromý, Jan; Borůvková, Marianna; Malá, Lucie; Sudzinová, Tereza (Attention, perception & psychophysics, 2019)
The aim of the article is to examine the stability of grapheme-colour matchings in adulthood. We carried out a panel study using computerized tests to measure short-term and long-term consistency. We conducted three testing rounds during 1 year and a half with a resulting sample of 26 synaesthetes. Our results suggest that the colours associated with individual graphemes can change substantially (e.g. from "salmon" to "aquamarine") even during this relatively short time period. Based on a linear mixed model, we further argue that short-term and long-term consistency should be distinguished because these scores tend to differ. These results thus complement previous findings on the issue of grapheme-colour consistency and have important consequences for the study of synaesthesia in the future.
Keywords: Synesthesia; dospělí; vnímání barev; Time Factors; časové faktory; lidé; Female; synestezie; mužské pohlaví; Perceptual Disorders; Male; Adult; Color Perception; Linear Models; ženské pohlaví; lineární modely; percepční poruchy; Humans